1977
DOI: 10.1002/ajh.2830030209
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the anemia and neutropenia of human copper deficiency

Abstract: Following extensive bowel resection, a young woman experienced severe malnutrition; subsequent administration of parenteral nutrition precipitated the copper deficiency syndrome. This consisted of hypocupremia, subnormal ceruloplasmin levels, anemia, and severe neutropenia. The bone marrow was megaloblastic, vacuolated, and sideroblastic; granulocytic maturation was not observed beyond the myelocyte stage. Copper sulfate therapy was followed by a marked reticulocytosis, increase in hematocrit, and recovery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 16 publications
1
49
0
Order By: Relevance
“…Dunlap et al (8) suggested that cytoplasmic vacuolization in early erythroid precursors is the first erythroid developmental change that occurs in cases of copper deficiency, because many patients with copper deficiency but without anemia exhibit this change. Most of the reported cases of copper deficiency (6,(8)(9)(10)(11)(12)(13)(14)(15), and all of the present copper-deficient subjects, exhibited cytoplasmic vacuolization of erythroid and myeloid precursors, which rapidly disappeared after copper supplementation. Although cytoplasmic vacuolization is also associated with other disorders, it may be particularly strongly associated with copper deficiency.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Dunlap et al (8) suggested that cytoplasmic vacuolization in early erythroid precursors is the first erythroid developmental change that occurs in cases of copper deficiency, because many patients with copper deficiency but without anemia exhibit this change. Most of the reported cases of copper deficiency (6,(8)(9)(10)(11)(12)(13)(14)(15), and all of the present copper-deficient subjects, exhibited cytoplasmic vacuolization of erythroid and myeloid precursors, which rapidly disappeared after copper supplementation. Although cytoplasmic vacuolization is also associated with other disorders, it may be particularly strongly associated with copper deficiency.…”
Section: Discussionmentioning
confidence: 64%
“…Copper deficiency has been observed in adult patients with inflammatory bowel disease (19,20), total parenteral nutrition (21,22), massive zinc ingestion (11) (6,(8)(9)(10)(11)(12)(13)(14)(15). Cytoplasmic vacuoles have also been found in patients with acute alcoholic intoxication (23), chloramphenicol toxicity (24), pancreatic dysfunction (25) and myeloproliferative syndromes (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe anemia and neutropenia are well-recognized signs of copper deficiency, resulting from ineffective erythropoiesis and granulopoiesis due to the arrest of progenitor cell maturation (45)(46)(47). Similar effects can be induced by using a high affinity copper chelator which decreases the intracellular copper content (48 had engraftment from the expanded cord at the time of engraftment while the rest engrafted from the unmanipulated unit.…”
Section: Copper Chelatorsmentioning
confidence: 78%
“…Although it is unclear why gender distribution of our patients showed more women than men (12 versus 1) (19)(20)(21)(22)(23), those with short bowel syndrome (24,25), and those with partial gastrectomy (12,26,27). In addition, sporadic case reports also suggested that inadequate diet alone or genetic disorders affecting proteins of copper metabolism could cause copper deficiency (28)(29)(30), including Menkes disease and occipital horn syndrome (10) …”
Section: Discussionmentioning
confidence: 99%